Investigation of the cytotoxic, anti-proliferative and anti-angiogenic effects of Toluhydroquinone on Caco-2 cell line - Kucak, Mine; Demir, Ummuhan; Muslumanoglu, M. Hamza (C M B ASSOC, 2022)
Colorectal cancer is one of the most common types of cancer in the world. The treatment options for colorectal carcinoma generally consist of surgery, radiotherapy and chemotherapy. The drug resistance to chemotherapy agents used in the current cancer treatment has brought about the finding of new drug molecules from some plant and aquatic species in the treatment approaches. Some species of aquatic biota create novel biomolecules as potential drugs for cancer and other diseases. Toluhydroquinone belongs to these groups of biomolecules and it shows anti-oxidative, anti-inflammatory and anti-angiogenic properties. In this study, we tested the cytotoxic and anti-angiogenic effects of Toluhydroquinone on Caco-2(Human colorectal carcinoma cell line) cells. It was observed that the amount of closure of the wound space, colony forming ability (in vitro cell survivability) and formation of tubule-like structures in matrigel decreased in comparison to the control group. As a result of this study, Toluhydroquinone has cytotoxic, anti-proliferative and anti-angiogenic properties on the Caco-2 cell line.Copyright (c) 2022 by the C.M.U .Association .All rights reserved.
Keywords: Toluhydroquinone; colon; cancer; angiogenesis; cytotoxic effect; anti-proliferative effect; APOPTOSIS; ASSAY; Biochemistry & Molecular Biology; Cell Biology